2016
DOI: 10.3389/fmicb.2016.01949
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Spatiotemporal Community Assembly Processes to Changes in Microbial Metabolism

Abstract: Community assembly processes generate shifts in species abundances that influence ecosystem cycling of carbon and nutrients, yet our understanding of assembly remains largely separate from ecosystem-level functioning. Here, we investigate relationships between assembly and changes in microbial metabolism across space and time in hyporheic microbial communities. We pair sampling of two habitat types (i.e., attached and planktonic) through seasonal and sub-hourly hydrologic fluctuation with null modeling and tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 91 publications
(72 citation statements)
references
References 74 publications
(96 reference statements)
9
63
0
Order By: Relevance
“…A subset of these taxa was present in comparable numbers in all three habitats, whereas others showed major variations connected to differential organic matter input and metabolism. Metabolically diverse heterotrophic Proteobacteria (31) were abundant in all the colonized sands, which is consistent with other hyporheic microbial communities (22,29,30) as well as previous Hanford 300 Area studies (15)(16)(17), and indicates a central role of these organisms in organic carbon (OC) decomposition across the HC. The abundance of Pseudomonadaceae relative to all Gammaproteobacteria was particularly high in the GWS, which is consistent with a previous sand colonization study in Hanford 300 Area groundwater (32), where Pseudomonadaceae accounted for 60 to 80% of all Proteobacteria.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A subset of these taxa was present in comparable numbers in all three habitats, whereas others showed major variations connected to differential organic matter input and metabolism. Metabolically diverse heterotrophic Proteobacteria (31) were abundant in all the colonized sands, which is consistent with other hyporheic microbial communities (22,29,30) as well as previous Hanford 300 Area studies (15)(16)(17), and indicates a central role of these organisms in organic carbon (OC) decomposition across the HC. The abundance of Pseudomonadaceae relative to all Gammaproteobacteria was particularly high in the GWS, which is consistent with a previous sand colonization study in Hanford 300 Area groundwater (32), where Pseudomonadaceae accounted for 60 to 80% of all Proteobacteria.…”
Section: Discussionsupporting
confidence: 88%
“…Although the sand packs did not reproduce in situ groundwater, riverbed, or hyporheic zone sediment properties, the sand is from the same geological (Hanford) formation and provided a clean substratum on which microbial community development as a function of in situ habitat could be assessed (16). NMDS analysis of the 16S rRNA gene amplicon libraries indicated that distinct attached microbial communities did in fact arise in the three different in situ colonization habitats (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of biogeochemical cycling in the parafluvial zone have sampled gravel bars to investigate hydrologic flow paths (Claret and Boulton, 2008;Deforet et al, 2009;Zarnetske et al, 2011) and have sampled during saturated conditions utilizing well/piezometer transects (Baker et al, 1999;Deforet et al, 2009;Briody et al, 2016;Graham et al, 2016;Stegen et al, 2016). Such studies have indicated that the parafluvial hyporheic zone is an active region of diverse biogeochemical transformations (Zarnetske et al, 2011;Briody et al, 2016) and microbial community dynamics (Baker et al, 1999;Graham et al, 2016Graham et al, , 2017Stegen et al, 2016), often influenced by residence times (Claret and Boulton, 2008;Deforet et al, 2009;Zarnetske et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have indicated that the parafluvial hyporheic zone is an active region of diverse biogeochemical transformations (Zarnetske et al, 2011;Briody et al, 2016) and microbial community dynamics (Baker et al, 1999;Graham et al, 2016Graham et al, , 2017Stegen et al, 2016), often influenced by residence times (Claret and Boulton, 2008;Deforet et al, 2009;Zarnetske et al, 2011). However, studies that have compared biogeochemical cycling in the parafluvial zone to other floodplain environments (e.g., forest, ponds, islands, wetlands) have found that stream and nearby gravel habitats have had lower respiration, bacterial abundance, enzyme activities, and sediment nitrogen nutrient leaching than adjacent pasture/grassland, vegetated islands, and/or mature forest habitats, but short flood pulses (24 h) have increased bacterial extracellular enzymes in sediment from both flooded riverbanks and wetlands (Burns and Ryder, 2001;Doering et al, 2011;Ostojić et al, 2013;Bodmer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%